PENGARUH KUALITAS AUDITOR DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Ridlo, Mukhlisur; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This study aimed to examine the effect of quality of auditor and corporate governance on earnings management in manufacturing companies. Quality of auditor in this study using the Big four auditors and auditors Non-Big four. Corporate governance in this study can be divided into three variabels, namely managerial ownership, institutional ownership, and the proportion of independent commissioners. Based on the results of the study showed that the quality of auditors and corporate governance is not significant. but in This study shows the data that the companies audited by auditors Big four showed a positive association between quality of auditor practice earnings management. Managerial ownership and institutional ownership are not significantly affect earnings management. the regulation on the proportion of the board of commissioners at the board causing the proportion of board of commissioners on the board of directors is only used as a formality and can reduce the level of objectivity in their work. Keywords: quality of auditor, corporate governance, earnings management.